ANALISIS MODIFIKASI DESAIN REAKTOR PADA RANCANG BANGUN ALAT PIROLISIS DAN PENGUJIAN NILAI KALOR UNTUK PLASTIK PP DAN ABS - Wijayanto, Rudi Purwo; Alhikam, Francois Rubian; Hendrawan, Iyus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The increasing use of plastic results in a rise in the volume of waste each year and has an impact on the environment. Pyrolysis is a method for recycling plastic waste into fuel oil. Improvements in pyrolysis design and techniques continue to be made to obtain better performance and optimal results. In this study, we compare the rate of increase in heat and volume of oil produced from two pyrolysis device designs. The alpha version is the previous version of the pyrolysis apparatus with a flat plate roof reactor and without the addition of an insulator on the tube wall. While the beta version is a modification of the alpha version with a conical roof reactor with the addition of calk material on the tube wall. Modification of the pyrolysis apparatus was also carried out in the condensation section. The beta version of the pyrolysis device shows better performance, where the reactor temperature reaches 250 ⁰C, while the alpha version, which is the previous version, reaches a maximum temperature of 220 ⁰C in a longer time. The volume of oil produced by the beta version is 0.11 mL/gram of polypropylene plastic, whereas the alpha version produced only 0.01 mL/gram for the same material. The test results for the calorific value of polypropylene (PP) plastic waste were 43.838 MJ/kg, while for acrylonitrile butadiene styrene (ABS) it was 44.772 MJ/kg.